Hubungan Keragamanan Makanan dengan Status Gizi Balita Usia 1-5 Tahun - Neng Yani Yulianti; Nendhi Wahyunia Utami; Endah Puji Astuti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Food diversity is a major problem for all developing countries, including Indonesia. Dietary diversity is associated with the risk of stunting and other nutritional problems. Stunting will have a negative impact on children's thinking, memory, school performance and work productivity in the future. In an effort to reduce the high stunting rate in Sumberwungu Village, the Government was distributing additional food in the form of snacks but it was not in accordance with nutritional needs. The aim of this research was to determine whether the nutritional status of toddlers aged 1-5 years was related to diversity in Sumberwungu Village, Tepus, Gunung Kidul, Yogyakarta. This type of research uses a retrospective methodology and is an analytical observational study. The sample in the research was 34 toddlers who experienced nutritional problems. Food diversity data was collected using the IDDS questionnaire with a non-consecutive 2x24 hour recall method. The data analysis used in this research is univariate and bivariate analysis. Bivariate analysis in this study uses the Kendal-Tau test to determine the relationship between food diversity and the nutritional status of toddlers. The results of data analysis showed that there was no relationship between food diversity and nutritional status in toddlers aged 1-5 years (z score BB/U p= 0.898, z score TB/U p= 0.941, and z score BB/TB p= 0.913).